Influence of post‑deposition annealing on the chemical states of crystalline tantalum pentoxide films - Perez, Israel (2018)
We investigate the effect of post-deposition annealing (for temperatures from 848 K to 1273 K) on the chemical properties of crystalline Ta2O5 films grown on Si(100) substrates by radio frequency magnetron sputtering. The atomic arrangement, as determined by X-ray diffraction, is predominately hexagonal ( − Ta2O5 ) for the films exposed to heat treatments at 948 K and 1048 K; orthorhombic ( − Ta2O5 ) for samples annealed at 1148 K and 1273 K; and amorphous for samples annealed at temperatures below 948 K. X-ray photoelectron spectroscopy for Ta 4f and O 1s core levels were performed to evaluate the chemical properties of all films as a function of annealing temperature. Upon analysis, it is observed the Ta 4f spectrum characteristic of Ta in Ta5+ and the formation of Ta-oxide phases with oxidation states Ta1+ , Ta2+ , Ta3+ , and Ta4+ . The study reveals that the increase in annealing temperature increases the percentage of the state Ta5+ and the reduction of the others indicating that higher temperatures are more desirable to produce Ta2O5 , however, there seems to be an optimal annealing temperature that maximizes the O% to Ta% ratio. We found that at 1273 K the ratio slightly reduces suggesting oxygen depletion.